ON THE QUESTION OF HISTORICAL RESEARCH METHODOLOGY: THE CASE OF STUDYING FOREIGN POLICY DECISION MAKING IN POST-WAR JAPAN - V. V. Nelidov (Сравнительная политика, 2018)
The article examines different variants of theoretical approaches to historical research, using the example of the analysis of foreign policy decision making in Japan during the rule of the Liberal Democratic Party (the “1955 system” period). These approaches are sorted by the degree of their generalizability. The difference in methodological approaches corresponds to the variation of epistemological positions, particularly, to the evaluations of possibility and usefulness of searching for regularities, existing irrespective of cultural and historical context. The conclusion is drawn that understanding the strengths and weaknesses of each of these approaches, as well as of the goals that can be set within their boundaries has significant importance for historical methodology.